2003
DOI: 10.1109/jmems.2003.809965
|View full text |Cite
|
Sign up to set email alerts
|

Low-order modeling of resonance for fixed-valve micropumps based on first principles

Abstract: Micropumps that utilize fixed-valves, i.e., valves having no moving parts, are relatively easy to fabricate and inherently reliable due to their simplicity. Since fixed-valves do not close, pumps based on them need to operate in a well-designed resonant mode in order to attain flow rates and pressures comparable with other designs. However, no methodology currently exists to efficiently investigate all the design parameters including valve size to achieve optimal resonant response. A methodology that addresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 20 publications
0
47
0
Order By: Relevance
“…Because microfluidic devices are required to be transparent and chemically inert for many bio-optical detection applications, we chose PMMA as the major structural material. Multiple mixing modules, which each contained two vortex micropumps, two Tesla valves [35,36] and an active micromixer (Figure 2(a)), were fabricated in a single microfluidic device using our process described in Methods; and a fabricated microfluidic device (top view dimensions: 42.5 mm × 60 mm) integrated with three mixing modules is shown in Figure 2(b). Each module was utilized to supply a chemical or reagent with a regulated concentration of the additive components.…”
Section: Design Of Microfluidic Mixing Module Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…Because microfluidic devices are required to be transparent and chemically inert for many bio-optical detection applications, we chose PMMA as the major structural material. Multiple mixing modules, which each contained two vortex micropumps, two Tesla valves [35,36] and an active micromixer (Figure 2(a)), were fabricated in a single microfluidic device using our process described in Methods; and a fabricated microfluidic device (top view dimensions: 42.5 mm × 60 mm) integrated with three mixing modules is shown in Figure 2(b). Each module was utilized to supply a chemical or reagent with a regulated concentration of the additive components.…”
Section: Design Of Microfluidic Mixing Module Arraymentioning
confidence: 99%
“…It should be mentioned that the Tesla microvalves (Figure 2(c)) located at the channel sections between the pumps and the mixers were applied to reduce potential backward flow since the backward fluidic resistance of the Tesla valve was comparatively higher than the forward one [36]. We performed computational analysis on the fluid flow in a Tesla valve to verify the flow resistance in different flow directions using commercially available software (COMSOL Multiphysics, COMSOL, Burlington, MA, USA).…”
Section: Design Of Microfluidic Mixing Module Arraymentioning
confidence: 99%
“…Micropumps fabricated with MEMS technology have been considered for use in such fuel transport mechanisms [16][17][18][19][20][21][22][23][24][25][26][27]. Liu et al reported polyimide (PI) diaphragm micropumps (15 × 15 mm 2 ) fabricated using MEMS technology [22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the soft diaphragm is compatible with the pumping of a liquid because liquid flow has high resistance and high kinetic energy. The flow rectification principles of valveless micropumps are usually based on the modification of the physical properties of fluids (5) or on flow-directing effects such as those found in diffuser elements (6)- (8) and Tesla elements (9) . Recently, a new channel structure to rectify flow without valves has been proposed (10)- (12) .…”
Section: Introductionmentioning
confidence: 99%